Commentary on the New Testament : verse-by-verse explanations with a literal translation - Gundry, Robert H. (Robert Horton), 1932- (Peabody, Mass. : Hendrickson Publishers, 2010)
Going beyond questions of authorship, date, sources, and historicity, respected linguist and teacher Gundry offers a one-volume exposition of the New Testament that focuses on what is most useful for preaching, teaching, and individual study--what the biblical text really means. Providing interpretive observations in a "breezy" style that's easy to read and adaptable for oral use in pulpit or classroom presentations, Gundry directs his book to an evangelical audience. --from publisher description
Introduction -- Matthew -- Mark -- Luke -- John -- Acts -- Romans -- First Corinthians -- Second Corinthians -- Galatians -- Ephesians -- Philippians -- Colossians -- First Thessalonians -- Second Thessalonians -- First Timothy -- Second Timothy -- Titus -- Philemon -- Hebrews -- James -- First Peter -- Second Peter -- First John -- Second John -- Third John -- Jude -- Revelation.
Keywords: Bible. -- Commentaries